O silêncio molhado dos dias: duoetnografia sobre a experiência da fibromialgia. - Renata Lopes Serra Negra (2024)
Fibromyalgia is a painful syndrome characterized by widespread chronic pain, sleep disturbances, profound fatigue and bilateral tender points. The intensity of symptoms is extremely variable, from person to person, ranging from mild, well-controlled conditions to more intense conditions, with negative repercussions on daily life activities. Chronic fatigue, failure to concentrate, body vibrating with pain, a bilateral relationship with mood and anxiety disorders, fibromyalgia is a complex condition that affects the mental and physical health of those who experience it. This project was developed with a qualitative approach based on the methodology of collaborative autoethnography, based on the theory of corporeality, in order to reveal the experience of fibromyalgia, in light of the socio-cultural experiences of two women. The production of autoethnographic data was carried out through field diaries and interactive interviews with another woman who experiences the pain of fibromyalgia and the main researcher, who shares these characteristics. Three major topics would emerge from the interviews and affective exchanges: delegitimization of fibromyalgia, feelings of anger, fear and guilt in the fibromyalgia experience and coping strategies. Our findings emphasized that fibromyalgia pain is ambiguous and invisible, raising questions of severity and legitimacy, especially when it comes to fat bodies . The subjective meaning of how the researchers experienced their symptoms on a daily basis revealed emotions as the central axis of the subjective experience. And the construction of coping strategies is based on the idea of community constructions, health education, art as a political expression of resistance and territorial roots. Provide an idea of overcoming through collective experience and practices. An exercise of the future.